Surfactant phosphatidylcholine composition during dexamethasone treatment in chronic lung disease. Issue 2 (September 1994) - Ashton, M R; Postle, A D; Smith, D E; Hall, M A
Abstract : Objectives - To determine whether dexamethasone `matures' the phosphatidylcholine (PC) composition of broncheoalveolar fluid in infants at high risk of neonatal chronic lung disease (CLD), either by increasing the proportion of dipalmitoylphosphatidylcholine (DPPC), expressed as a percentage of total PC (%DPPC), or by increasing the ratio of DPPC to palmitoyloleoylphosphatidylcholine (DPPC:POPC ratio). Design - Double blind, placebo controlled. Setting and patients - Sixteen infants <32 weeks' gestation, <1250 g birth weight who were dependent on mechanical ventilation and requiring a fractional inspired oxygen of >0·30 at 12 days of chronological age. Intervention - Randomisation to receive a two week reducing course of dexamethasone base at an initial dose of 0·2 mg/kg three times a day, or equivalent volumes of normal saline, starting at 14 days. Eight infants were randomised into each group. Broncheoalveolar lavage was performed serially throughout the study period or until extubation. PC composition of the fluid was analysed by high performance liquid chromatography. Outcome measures - The %DPPC and the DPPC:POPC ratios were calculated for individual infants for days −1 and 0 combined, days 1 and 3 combined, and days 5 and 7 combined. Analysis of covariance was used to analyse the results. Results - The DPPC:POPC ratio was significantly less in the treated group than the placebo group on days 1 and 3, and not greater as the hypothesis stated. Three out of five infants treated with dexamethasone and for whom data were available showed a substantial rise in DPPC:POPC ratio on days 5/7, compared with the placebo group, but overall these changes were not statistically significant. Conclusions - The data do not support the hypothesis that dexamethasone's action in producing a clinical improvement within the first 72 hours of treatment for neonatal CLD is by the `maturation' of pulmonary surfactant PC.